If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x = 10 + -1x Solving -6x = 10 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -6x + x = 10 + -1x + x Combine like terms: -6x + x = -5x -5x = 10 + -1x + x Combine like terms: -1x + x = 0 -5x = 10 + 0 -5x = 10 Divide each side by '-5'. x = -2 Simplifying x = -2
| -7(a+2)+15=1-7a | | 2-y=x-6 | | 2-(15-7)*7= | | 3-3=0.03703703703 | | 8-5+2-4+7*6= | | 1-0.75x-0.3x^2=0 | | e=3(8)+3(8) | | 5(t-3)-2t=3t-8 | | 5y+29=5+25 | | -8+5r=5r-r | | 18=21x-6y | | 99+5x=2000+-5x+911 | | 75-50x+6x^2=0 | | 15f-8f+13=-14 | | -7-7n=-6n-2n | | -32f-12g=48 | | 2(9-7s)= | | -5*y=x^2 | | 2r-y-6=0 | | 4k(7k+5)= | | 12b^2-8=6b | | X+(-4)=-7 | | -10+2x=3x-1+8x | | 12b^2-8=ab | | x^2(x+7)=40x+100 | | (y^2)-23y+130=0 | | 7n+20=6 | | 200-6x=500-6x | | 4n+3+20=6 | | -16t^2+5t+92=0 | | Y+-3=8 | | 0=9x+25+5y |